EMPATHY-BASED ISLAMIC RELIGIOUS EDUCATION AS A STRATEGY FOR FOSTERING SPIRITUAL AWARENESS AND STUDENT RESILIENCE AMID SOCIAL MEDIA CHALLENGES - Nasir; Asmawati; J.M. Ekafitrianda (Academic Bright Collaboration, 2026)
This study aims to analyze the moral challenges experienced by students in the social media era and to reconstruct an empathy-based Islamic Religious Education (IRE) framework designed to strengthen students' resilience and spiritual awareness. The study employed a qualitative library research design by systematically examining scholarly journal articles, books, policy documents, and relevant academic literature on Islamic education, social media, empathy, resilience, and spiritual development. Data were analyzed using qualitative content analysis involving data reduction, thematic categorization, interpretation, and conceptual synthesis. The findings indicate that students' moral challenges are shaped by the interaction of weakened religious value internalization, limited social supervision, and the dominance of individualistic digital culture. Based on this synthesis, the study proposes an empathy-based learning framework consisting of dialogic learning, structured spiritual reflection, teacher role modeling, experiential social learning, and the integration of Islamic digital literacy into classroom practices. Rather than functioning solely as moral instruction, this framework positions empathy as the pedagogical foundation for nurturing students' resilience, ethical decision-making, and spiritual awareness within contemporary digital environments. This study is conceptual in nature and is based on qualitative library research; therefore, the proposed framework has not yet been empirically validated in classroom settings. Future studies are encouraged to examine its effectiveness through quantitative, mixed-method, or intervention-based research across diverse educational contexts. This study contributes a conceptual model that enriches the discourse on Islamic Religious Education by integrating empathy, resilience, spirituality, and digital literacy into a coherent pedagogical framework for the social media era, addressing a gap in previous studies that have largely examined digital literacy and moral education separately.